2022
DOI: 10.3390/nu14183847
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Spermidine and TyG Index: Results from a Cross-Sectional Study

Abstract: Background: Although animal experiments have shown that spermidine (SPD) affects insulin resistance (IR), the evidence for this in humans is still scarce. We aimed to investigate the associations between serum SPD levels and the TyG index in the adult population. Methods: A cross-sectional study was carried out with 4336 participants, all of whom were adults aged 35+ years. The SPD levels in serum were detected using high performance liquid chromatography with a fluorescence detector (HPLC-FLD). The triglyceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Therefore, due to the differences in race, gender, study population, and health status, criteria for assessing insulin resistance are often inconsistent, and establishing a universal normal range remains a problem. In previous studies, it is recommended that the upper quartile of insulin resistance (or the lower quartile of insulin sensitivity) of the specific population under a study be used as the cutoff for insulin resistance, regardless of the test method (26)(27)(28). As markers of insulin resistance, the higher the TyG index and HOMA-IR, the higher the level of insulin resistance.…”
Section: Definitionsmentioning
confidence: 99%
“…Therefore, due to the differences in race, gender, study population, and health status, criteria for assessing insulin resistance are often inconsistent, and establishing a universal normal range remains a problem. In previous studies, it is recommended that the upper quartile of insulin resistance (or the lower quartile of insulin sensitivity) of the specific population under a study be used as the cutoff for insulin resistance, regardless of the test method (26)(27)(28). As markers of insulin resistance, the higher the TyG index and HOMA-IR, the higher the level of insulin resistance.…”
Section: Definitionsmentioning
confidence: 99%
“…Similar to the findings in animals, spermidine calculated from dietary intake in a general population of National Health and Nutrition Examination Survey (NHANES) from 2009 to 2010 was negatively associated with serum glucose, insulin, HbA1C levels, and homeostatic model assessment of insulin resistance (HOMA-IR) index ( 15 ). Furthermore, our population-based study showed serum spermidine was inversely associated with triglyceride-glucose index and the risk of insulin resistance ( 16 ). However, to our knowledge, the associations between spermidine and T2DM and fasting plasma glucose (FPG) has not been fully explored.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to HHcy, insulin resistance (IR) was likewise found as one of the main contributors to CVD, 20 which is regarded as an insulin-regulated defect in tissue glucose metabolism control. 21,22 The "gold standard method" for IR assessing is hyperinsulinemic-euglycemic clamp, [23][24][25] and its alternative method was Homeostatic Model Assessment (HOMA-IR) by calculating insulin and glucose levels to determine IR. 26 However, these tests are so expensive and complex to detrimentally restrict their wide use.…”
Section: Introductionmentioning
confidence: 99%